Past Decade Work Done on Cubosomes and its Factorial Design: A Fast Track Information for Researchers: Pharmaceutical Science-Industrial Pharmacy - Shravani Y; Hindustan Abdul Ahad; Chinthaginjala Haranath; Bhumireddy gari Poojitha; Syed Rahamathulla; Aswarthanarayana Rupasree (International Journal of Life Science and Pharma Research, 2022)
The objective of this review is to explore the past work done on Cubosomes as drug delivery systems by factorial design. Cubosomes are Nanoparticulate systems made of amphiphilic lipids at a certain percentage, known as liquid crystals. They have tightly packed honeycomb structures twisted into 3D bilayers. Cubosomes can capture all categories of the lipophilic, hydrophilic, and amphiphilic substances irrespective of their affinity, by that they fit for delivering all range of drugs with ease. Many works in recent days are concentrating on Cubosomes for drug delivery, as it suits all ranges of drugs without much difficulty. Cubosomes acts as a carrier in drug delivery for a wide range of drugs and protects them from degradation issues like hydrolysis, oxidation, and others. Moreover, numerous studies have established the benefits of Cubosomes in nanotechnology, prolonged-release, and also enhanced bioavailability. This article reviews about the past work done on Cubosomes using factorial design. Additionally, many studies need to be performed for the optimization of Cubosomes for artificial cells, and biosensors, etc. Moreover, the rational design of Cubosomes for biomedical applications need to be developed. A widespread literature assessment revealed that many reviews and research attempts were made on Cubosomes, but no review article is still available in bringing the attempts made on Cubosomes by factorial design on a single platform. The factorial approach is used to optimize the formulation, which is acceptable and used in the current scenario in optimizing the formulations. So, the authors made widespread work by referring to peer-review journals, periodicals, magazines, and succeeded in bringing work done on Cubosomes in the last ten years by using factorial design. The study concludes and gives a quick reference to the young researchers to get literature on earlier successive attempts done on Cubosomes by factorial design.